(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Laser source is one of the most important components of a laser marking system, others being its scanner and control unit. Laser source is characterized by its output parameters, i.e., factors that define the source and determine its limits. In this study averge laser power, pulse repetition frequency, pulse duration, pulse peak power, and, most importantly, pulse energy are analyzed in order to better determine capabilities of a system.